2022
DOI: 10.1182/blood.2021015020
|View full text |Cite
|
Sign up to set email alerts
|

Engineering naturally occurring CD7− T cells for the immunotherapy of hematological malignancies

Abstract: Chimeric antigen receptor (CAR) T cell therapy targeting T-cell acute lymphoblastic leukemia (T-ALL) faces limitations such as antigen selection and limited T-cell persistence. CD7 is an attractive antigen for targeting T-ALL, but overlapping expression on healthy T cells leads to fratricide of CD7-CAR T cells, requiring additional genetic modification. We took advantage of naturally occurring CD7- T cells to generate CD7-CAR (CD7-CARCD7-)T cells. CD7-CARCD7- T cells exhibited a predominantly CD4+ memory pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The above study demonstrated the persistence of naturally selected CD7 CAR T cells in the in vitro phase of the study. However, further validation of its durability in comparison with other reported CD7 CAR-T cells and in clinical trials of R/R-AML needs to be performed [15,[51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above study demonstrated the persistence of naturally selected CD7 CAR T cells in the in vitro phase of the study. However, further validation of its durability in comparison with other reported CD7 CAR-T cells and in clinical trials of R/R-AML needs to be performed [15,[51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CD7 CAR-Ts may be less costly and exhibit lower risks associated with gene editing. In addition, in recent years, the construction of CAR-T cells by isolating CD7-negative cell populations or the use of ibrutinib and dasatinib to inhibit fratricide has demonstrated good potential value [52,54]. Hai-Ping Dai et al demonstrated the safety and efficacy of CD7 CAR-T cells using protein expression blockers to block CD7 expression at the CAR-T-cell membrane for the treatment of R/R early T-cell precursor lymphoblastic leukaemia/lymphoma (ETP-ALL/LBL) in patients with TP53 mutations [51].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, they are predominantly CD4+ effector memory and CD4+ and terminally differentiated effector memory cells with a preserved expansion activity and viability. Moreover CD7 CAR-T cells are characterized by an effective antitumor immune response, as demonstrated by their ability to kill both CD7 and CD19 expressing haematological malignant cells [ 103 ].…”
Section: T-cell Surface Antigens As Immunotherapeutic Target For T-allmentioning
confidence: 99%
“…In another study, Freiwan et al. sorted CD7- T cells from PBMC before transducing them with CD7 CAR, the CD7- CAR-T cells contained more CD4+ memory phenotype and have a robust antitumor activity to CD7+ cell lines CCRF-CEM and MOLT3 in vitro and eliminated CCRF-CEM cells in the mouse model, as well as bypass fratricide ( 89 ). Li et al.…”
Section: Car-t Therapy For Non-b-cell Acute Leukemiamentioning
confidence: 99%